2004
DOI: 10.1016/j.jasms.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Carbocationic rearrangement of pivaloyl cation and protonated pivalaldehyde in superacid medium: A novel solution equivalent of the McLafferty rearrangement

Abstract: Both pivaloyl cation in the presence of hydride donors and protonated pivalaldehyde in superacid media (both aprotic and protic) rearrange to protonated methyl isopropyl ketone involving gitionic dicationic intermediates. In our earlier studies we have found that the rearrangement of pivaladehyde to methyl isopropyl ketone occurs quantitatively in the presence of various superacidic media such as anhydrous HF, triflic acid, boron trifluoride-2,2,2-trifluoroethanol complex (BF 3 ⅐2CF 3 CH 2 OH) etc. Our present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…At 50 eV, the ions of m/z 575, 391 and 207 were the main product ions from sodiated nonactin. Accurate‐mass measurements revealed that these fragments derived from losses of one, two and three C 10 H 16 O 3 (184 mass units) molecules from the precursor ion ([M + Na] + ), respectively, via consecutive McLafferty‐type rearrangements (Scheme ) . These reactions had been previously described for other polyether ionophores, such as lasalocid and tetronasin .…”
Section: Resultsmentioning
confidence: 99%
“…At 50 eV, the ions of m/z 575, 391 and 207 were the main product ions from sodiated nonactin. Accurate‐mass measurements revealed that these fragments derived from losses of one, two and three C 10 H 16 O 3 (184 mass units) molecules from the precursor ion ([M + Na] + ), respectively, via consecutive McLafferty‐type rearrangements (Scheme ) . These reactions had been previously described for other polyether ionophores, such as lasalocid and tetronasin .…”
Section: Resultsmentioning
confidence: 99%
“…Loss of the t-butyl radical followed by McLafferty rearrangement does not seem plausible for the first loss would create an even electron ion. Although the McLafferty rearrangement has been observed for even electron systems [21,22,24,25,[30][31][32]36,41,46,49,60] , it seems unlikely to be of great importance for these systems, but it cannot be excluded for we did not investigate this possibility in more detail. The loss of just the t-butyl radical was also observed as the peaks at the highest m/z values, as well as abundant formation of [HOSi(CH 3 ) 2 ] + (m/z = 75).…”
Section: Resultsmentioning
confidence: 99%
“… The study of the major MS fragmentations of these carbonyl derivatives, however, has not received due attention. For example, although the McLafferty rearrangement of carbonyl compounds has been the focus of extensive and continuous research , studies on oximes and silyl oxime ethers have been limited. Surprisingly, to date, only one article has reported the McLafferty rearrangement for ketoximes.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts of these types are also suitable for complete isomerization of pivalaldehyde to methyl isopropyl ketone (62). The mechanism of the carbocationic rearrangement under superacidic activation in solution is believed to be similar to the McLafferty rearrangement reported in the gaseous phase.…”
Section: Alkylation Catalystsmentioning
confidence: 91%